2012
DOI: 10.1007/s10461-012-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Optimizing Clinic Efficiency in a Community-Based Antiretroviral Treatment Programme in Uganda

Abstract: We address a critical aspect of antiretroviral therapy (ART) scale-up: poor clinic organization leading to long waiting times and reduced patient retention. Using a before and after study design, time and motion studies and qualitative methods we evaluated the impact of triage and longer clinic appointment intervals (triage) on clinic efficiency in a community-based program in Uganda. We compared time waiting to see and time spent with providers for various patient categories and examined patient and provider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Differentiated HIV care has been proposed to provide appropriate care to different populations within clinics. The modest body of rigorous evidence on differentiated care to date, however, largely focuses on strategies for stable patients [30][31][32][33][34][35][36]. Far less has been written about strategies for unstable patients, a population much harder to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated HIV care has been proposed to provide appropriate care to different populations within clinics. The modest body of rigorous evidence on differentiated care to date, however, largely focuses on strategies for stable patients [30][31][32][33][34][35][36]. Far less has been written about strategies for unstable patients, a population much harder to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Together, task shifting and reduction of intensity of follow up achieved saving of large number of physicians' consultations (41, 116 physician visits averted in 2014), creating extra physicians' time for co-morbid, severely sick or patients failing ART. Research conducted by Alamo et al presents evidence that such approaches improve patient flow, reduce waiting time and increase patients' and providers' satisfaction [10]. At the same time, studies conducted in similar urban context of Uganda show that facility-based interventions are cost-effective and have positive effect on patient'sa d h e rence [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The MSF facilitybased model of care was designed to optimize HIV care by differentiating ART delivery according to age and clinical characteristics, thereby allowing programs to save specialized expertise for the management of complicated cases with severe co-morbidities. The model was based on existing evidence for the facility based differentiated models showing good treatment outcomes with improved adherence, increasing patient and staff satisfaction, reduction of waiting time and service delivery for more patients with the same number of staff [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…More important, this may also indicate that facility‐based delivery still has higher absorptive capacities waiting to be utilized. Studies have shown that strategies to remove facility‐level barriers (such as reduction in long waiting times) in antiretroviral treatment programmes often result in increased uptake of treatment . While scaling up ART access through community approaches is important, the opportunities for improving facility ART uptake should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%